Compiling a national register of babies born with anophthalmia/microphthalmia in England 1988–94. Issue 3 (1st November 1998) - Busby, Araceli; Dolk, Helen; Collin, Richard; Jones, R Barry; Winter, Robin
Abstract : AIM: To describe the prevalence of anophthalmia/microphthalmia in babies born in England 1988–94, as well as their overall survival, and the incidence of associated eye and non-eye malformations; to determine the usefulness of different sources of medical and health service information for establishing a retrospective register of anophthalmia/microphthalmia. METHODS: Multiple sources for initial (retrospective) case ascertainment were surveyed, followed by questionnaires to clinicians to establish severity, associated malformations, and aetiology for England, 1988–94. The population surveyed was all births in England for this time period (4 570 350 births). Cases included live births, stillbirths, or terminations after prenatal diagnosis of congenital anomaly, with anophthalmia/microphthalmia, with or without other malformations and syndromes. Trisomy 13 was subsequently excluded. RESULTS: The proportion of cases notified by any one information source was not more than 26% (Office for National Statistics Register 22%, paediatricians 26%, district sources 25%). Sixty nine per cent of cases (51% of severe cases) were notified by only one source. A total of 449 cases were reported, prevalence 1.0 per 10 000 births. The prevalence was stable over time, although the proportion notified by clinicians rose in more recent years. Thirty four per cent of affected babies had mild microphthalmia. Of those with severe anophthalmia/microphthalmia, 51% were bilateral, other eye malformations were present in 72%, non-eye malformations in 65%, and a "known aetiology" was attributed in 22%. Three quarters of those severely affected survived infancy. CONCLUSIONS: Despite high response rates from the sources of information contacted, the lack of duplication between sources indicates the difficulties of retrospective ascertainment and the need for multiple sources when establishing a register. Anophthalmos/microphthalmos is usually associated with other malformations. Most cases are of unknown aetiology.